The Assessment of Comunication and Interaction Skills in Psychotic Patiens - Katayoun Khoushabi; Samira Keyvani (University of Social Welfare and Rehabilitation Sciences, 2002)
Objective: The main objective at study was to assess the communication and interaction of psychotic patient above age of 18 in 2000. Materials & Methods: The study sample consist of 80 psychotic patients (38 female and 42 male) from Razi and Imam Hossein Hospital and Raad and Sina outpatient clinic, selected based on occupational therapist using the Assessment of Communication and Interaction Skills Questionnaire (ACIS). Statistical analyses of information have done by spearman coefficient correlation, Mann Whitney and Wilcoxon tests. Results: Spearman of correlation, mann-and wilcoxon Findings indicate: 1-The average grade of ACIS test in the group of schizophrenic patients were significantly lower than the group schizoaffective patients (P<0.00l). 2-The average of ACIS test in the group of inpatient was lower than the group of outpatient (p<0.00l). 3-No significant difference was found for the average grade of ACIS test in the group of male & female. Conclusion: The obtained results show the weakness of communication and interaction skills in schizophrenic patient and also inpatients. The obtained results of this investigation give useful information about the communication and interaction skill of patient to the occupational therapists but application of this instrument needs more studies.